The Effect of Iron and Folic Acid Supplementation on Adolescent Mental Health - Dewi Ari Sasanti; Leni Suhartini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Depression significantly impacts multiple aspects of life, including relationships, academic or work performance, and overall well-being. Individuals who have experienced abuse, severe loss, or other stressful events are more susceptible to depression. The aim of this study was to determine the effect of iron and folic acid supplementation on the mental health of adolescents. This research is a quantitative research using pre-experimental design, one-group pre-post test design research type. The sampling method in this study used purposive sampling with a sample size of 30 people. Researchers collected respondent data by gathering them in one room, providing an initial questionnaire. The researcher explained how to take Fe and folic acid tablets to the respondents. Respondents were instructed to write down the date in a table provided by the researcher after taking their iron tablets as scheduled. The researcher and respondents agreed on a meeting date one month later to complete the same questionnaire as the first. The results of the Wilcoxon Signed Rank Test statistical test show that the Asymp.Sig. (2-tailed) value is 0.001, because the significance value of the test results is 0.001 (α <0.05), so the hypothesis (Ha) is accepted and the hypothesis (H0) is rejected. So it can be concluded that there is a significant influence on the provision of Iron and Folic Acid supplementation on adolescent mental health. The conclusion of this study is that respondents who adhere to the schedule for taking Fe and Folic Acid tablets have a good impact on mental health.